2019
DOI: 10.13075/ijomeh.1896.01466
|View full text |Cite
|
Sign up to set email alerts
|

The health impact of Saharan dust exposure

Abstract: Air pollution is a high priority global health concern. The health damaging effects of ambient particulate matter (PM), a component of air pollution, are extensively documented, with 1.4% of deaths worldwide resulting from exposure to PM. A growing body of evidence suggests that mineral dust, found in PM, may contribute to some of these deleterious health impacts. Approximately half of atmospheric mineral dust originates from the Sahara Desert. This systematic but concise review summarizes the findings from re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…Moreover, dust is also associated with the risk of other diseases, including pulmonary infectious [ 51 , 52 ] and cardiovascular diseases [ 53 ]. PM has been shown to directly contribute to all-cause and cause-specific mortality as well [ 54 ]. For example, a study in Barcelona showed that a daily increase of 10 μg/m 3 in PM 10–2.5 from Saharan dust was associated with an 8.4% increase in mortality [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dust is also associated with the risk of other diseases, including pulmonary infectious [ 51 , 52 ] and cardiovascular diseases [ 53 ]. PM has been shown to directly contribute to all-cause and cause-specific mortality as well [ 54 ]. For example, a study in Barcelona showed that a daily increase of 10 μg/m 3 in PM 10–2.5 from Saharan dust was associated with an 8.4% increase in mortality [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to such PM plays a key role in cardiovascular disorders attributed to air pollution [2]. The World Health Organization (Geneva, Switzerland) recommends that the population should not be exposed to concentrations of breathable PM with an aerodynamic diameter <10µm, i.e., PM10, of over 50µg/m 3 .…”
Section: Introductionmentioning
confidence: 99%
“…At present, part of the scientific community is investigating the health consequences of the inhalation of airborne desert dust as a component of PM10 breathable particles, which affects over 2000 million people [3]. The main dust-emitting regions are found in the so-called Dust Belt, which extends through North Africa, the Middle East, and Inner Asia (Figure 1) [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PM deriving from Saharian dust are responsible to multiple causes of mortality and morbidity. The impact of dust is appearing and sufficiently powerful, therefore it requires further study [9]. As found from these previous papers, the use of air purifier to reduce PM levels, seems an appealing solution.…”
Section: Introductionmentioning
confidence: 99%